Pengaruh paparan cahaya biru layar digital terhadap kualitas tidur dan fungsi kognitif - Ulyani, Nadiyya (Maliki Interdisciplinary Journal, 2026)
The increasing use of digital devices has made exposure to blue light from screens a common part of daily activities, especially at night. This situation raises concerns about possible effects on sleep quality and cognitive performance. This study aims to examine how blue light exposure from digital screens may influence sleep quality and cognitive functions, including attention, memory, concentration, and the ability to process information. The discussion was carried out by reviewing various scientific sources related to digital device use, sleep patterns, and cognitive abilities. The findings indicate that nighttime exposure to blue light tends to be linked to delayed sleep time, reduced sleep comfort, and changes in rest patterns that may affect physical and mental condition the next day. Ongoing sleep disturbances may also contribute to lower focus, decreased accuracy, and reduced performance in tasks requiring concentration. However, in certain situations, blue light exposure may provide short-term benefits by increasing alertness, particularly during daytime activities. Therefore, the impact of blue light cannot be viewed in a simple way, as it is influenced by exposure time, duration of device use, and individual habits. This study is expected to provide insight into developing healthier digital device habits to help maintain sleep quality and cognitive function.